2016
DOI: 10.1155/2016/1429286
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Base Materials Regarding Their Effect on Root Canal Treatment Success in Primary Molars with Furcation Lesions

Abstract: Introduction. The aim of this study was to compare MTA with another base material, IRM, which is generally used on pulpal floor after root canal treatment, regarding their effect on the success of root canal treatment of primary teeth with furcation lesions. Materials and Methods. Fifty primary teeth with furcation lesions were divided into 2 groups. Following root canal treatment, the pulpal floor was coated with MTA in the experimental group and with IRM in the control group. Teeth were followed up consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…In addition, this method allows for precise control of the material to be tested, decreasing the variability in the study compared with other techniques. Furthermore, this method allows for the measurement of the fibrous capsule's thickness, which is a good marker of inflammation , assists in evaluating the biocompatibility of various materials, and is considered a validated method because clinical studies have shown results similar to those previously observed in subcutaneous implantation studies .…”
Section: Discussionmentioning
confidence: 98%
“…In addition, this method allows for precise control of the material to be tested, decreasing the variability in the study compared with other techniques. Furthermore, this method allows for the measurement of the fibrous capsule's thickness, which is a good marker of inflammation , assists in evaluating the biocompatibility of various materials, and is considered a validated method because clinical studies have shown results similar to those previously observed in subcutaneous implantation studies .…”
Section: Discussionmentioning
confidence: 98%
“…In addition, placement of ProRoot MTA on the pulpal floor of primary teeth with furcation radiolucencies was reported to decrease the healing period (Arikan et al . ).…”
Section: Root Fillingmentioning
confidence: 97%
“…Radiographic characteristics of the root and supporting structures (Arikan, Sonmez, & Sari, ; Pandranki, NR, & Chandrabhatla, ): The extension of radiolucency at the furcation area did not exceed the half of the space between the furcation and the permanent successor No internal root resorption External root resorption (Physiologic or pathologic) limited to apical third and with at least two‐thirds root intact …”
Section: Methodsmentioning
confidence: 99%
“…Their age ranged from 4 to 6 years. (Arikan, Sonmez, & Sari, 2016;Pandranki, NR, & Chandrabhatla, 2018):…”
Section: Study Subjectsmentioning
confidence: 99%